1985
DOI: 10.1111/j.1469-8137.1985.tb02879.x
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF WATERLOGGING ON SEEDLINGS OF EUCALYPTUS MARGINATA

Abstract: SUMMARYThree-to four-month-old Eucalyptus marginata Donn ex Sm. (jarrah) were grown in the glasshouse in peat/sand at 20 °C root temperature, and either waterlogged continuously for up to 14 d, or waterlogged for a shorter time and then drained. During waterlogging, the Og concentration ofthe soil solution declined to less than 1 mg 1~* within 1 d. There was an increase in the resistance to water movement into or through the plant within 4 d of flooding the pots. The number of xylem vessels blocked by tyloses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 17 publications
0
45
0
Order By: Relevance
“…Our work has shown that increased sporulation and growth of P. cinnamomi will not occur in waterlogged soil because aeration is inadequate (Davison & Tay, 1986). Waterlogging, however, directly affects the host because when glasshousegrown jarrah seedlings are flooded the xylem vessels in the root and stem become blocked with tyloses, and as the plants continue to transpire they eventually wilt and die (Davison & Tay, 1985). In this paper we examine the efTect of short-term waterlogging on infection of jarrah seedlings by P. cinnamomi.…”
Section: Introductionmentioning
confidence: 99%
“…Our work has shown that increased sporulation and growth of P. cinnamomi will not occur in waterlogged soil because aeration is inadequate (Davison & Tay, 1986). Waterlogging, however, directly affects the host because when glasshousegrown jarrah seedlings are flooded the xylem vessels in the root and stem become blocked with tyloses, and as the plants continue to transpire they eventually wilt and die (Davison & Tay, 1985). In this paper we examine the efTect of short-term waterlogging on infection of jarrah seedlings by P. cinnamomi.…”
Section: Introductionmentioning
confidence: 99%
“…As tylosed vessels contain air not water they are no longer able to conduct water (Zimmermann 1983). Most tree seedlings close their stomata when they are waterlogged, but jarrah does not and continues to transpire (Davison and Tay 1985). Consequently during summer, when transpiration rates are high, seedlings wilt and die (Fig.…”
Section: Waterlogging Damagementioning
confidence: 99%
“…When seedlings are waterlogged the xylem vessels in the tap root rapidly cavitate and become occluded with tyloses (Fig. 6), with the proportion of tylosed vessels being proportional to the duration of flooding (Davison and Tay 1985). As tylosed vessels contain air not water they are no longer able to conduct water (Zimmermann 1983).…”
Section: Waterlogging Damagementioning
confidence: 99%
See 2 more Smart Citations